2014
DOI: 10.1007/s00595-014-0984-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between obesity and clinicopathological factors in patients with papillary thyroid cancer

Abstract: In PTC patients ≥45 years of age, a higher BMI was associated with more aggressive tumor features, such as lymph node metastasis, lymphatic invasion, and tumor multiplicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…[1416,18,24] Our study has shown at the first time that higher BMI is strongly associated with extra-thyroidal invasion and universally associated with multifocality, advanced TNM staging, and primary tumor size >1 cm in our study. Further, those had been shown at the same time in the overweight group and/or in the obese group.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…[1416,18,24] Our study has shown at the first time that higher BMI is strongly associated with extra-thyroidal invasion and universally associated with multifocality, advanced TNM staging, and primary tumor size >1 cm in our study. Further, those had been shown at the same time in the overweight group and/or in the obese group.…”
Section: Discussionsupporting
confidence: 51%
“…[13] Some studies suggested that obesity was significantly associated with larger tumor size and marginally associated with advanced tumor stage. [14,15] At the same time, Kim et al [16] believed that the correlation between the 2 was found in a specific group of patients ≥45 years of age. In Chinese population, Liu et al [17] found that increased BMI might elevate the risks of aggressive clinicopathological features, such as extrathyroidal invasion and advanced TNM stage.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also confirmed an association between obesity and increased risk for thyroid cancer. Obesity may influence tumor size and extrathyroidal invasion, and may increase aggressiveness and metastasis of cancer (Kim et al, 2015;Ma et al, 2015). In agreement with our study, Guignard et al (2007) found no evidence between alcohol consumption and thyroid cancer risk in New Caledonia (Oceania) population.…”
Section: Discussionsupporting
confidence: 88%
“… 36 , 37 Previous investigations have suggested that obesity is a potential inducer of PTC tall cell variants, 38 changes in iodine uptakes, more frequent mutations in BRAF (V600E) genes, and the transformation of a normal phenotype to a malignant one in thyroid cells or more aggressive forms of PTC. 38 , 39 More evidence is needed to determine the precise mechanisms of the link between weight change during adulthood and PTC risk, particularly regarding the risk of PTC with a more aggressive tumor presentation.…”
Section: Discussionmentioning
confidence: 99%